GENERAL GEOLOGY AND ENGINEERING GEOLOGY, KM76 - KM61 LOJING-GUA MUSANG ROAD, KELANTAN - MOHD AKHIR, NADIRA WAHIDA (2016)
Lojing-Gua Musang road, Kelantan from Km76 to Km61 is the study area for the clarification of the geological structures by detailed geological mapping as well as to conduct engineering geology mapping and to determine rock slope stability and rock mass rating. Thus, comprehensive fieldwork investigations have been conducted in the study area and there are 3 outcrops that have been investigated along this road. This first outcrop located at km76 is identified as coarse grain granite, the second outcrop located at km61 is composed of fine grain granite while the last outcrop is a quartz mica schist and is the contact zone with the granite. Besides, based on this study, outcrop 1 and 2 have similar direction of maximum stress which is directed in the north-east direction while the third outcrop’s maximum stress in the east-ward direction.